Metal-doped biomimetic mineralized dECM crystal gel as well as preparation method and application thereof
By preparing metal-doped biomimetic mineralized dECM crystal gel, the shortcomings of existing bone tissue engineering scaffolds in terms of microscopic and macroscopic structural generalization are solved, and osteogenic and vascularization effects are achieved in the bone regeneration process, with high biocompatibility and cell activity.
Patent Information
- Application Number
- CN202511075821.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2025-10-31
AI Technical Summary
Existing bone tissue engineering scaffolds cannot accurately represent the bone from its microscopic composition to its macroscopic structure, and decellularized extracellular matrix materials destroy the organic-inorganic composite structure during the removal of cellular components, affecting the bone regeneration effect.
A metal-doped biomimetic mineralized dECM gel was prepared by mixing hyaluronic acid and methacrylic anhydride in a solvent, crosslinking with decellularized extracellular matrix under photoinitiator conditions, soaking in a mineralization solution containing Ca2+ and/or Mg2+, adding phosphate ion buffer, and incubating to obtain a gel with an oriented structure.
It achieves a detailed generalization of the composition and multi-layered structure of natural bone from the microscopic to the macroscopic level, promotes osteogenic and vascularization in the bone regeneration process, and has high biocompatibility and superior cell activity.
Smart Images

Figure BDA0005529304900000061 
Figure BDA0005529304900000071 
Figure HDA0005529304910000011
Abstract
Description
Technical Field
[0001] This invention relates to the field of bone tissue materials technology, and in particular to a metal-doped biomimetic mineralized dECM crystal gel, its preparation method and application. Background Technology
[0002] Constructing tissue-engineered scaffolds that mimic the structure of natural bone tissue is a key focus of current biomimetic bone tissue engineering strategies. However, the composition and structure of bone tissue are extremely complex. At the microscopic level, the extracellular matrix (ECM) is a complex structure composed of mineralized collagen, in which apatite nanocrystals are deposited along collagen fibers and arranged in a periodic, staggered pattern along the fibrils. Bone tissue also contains various types of non-collagenous matrix proteins, such as glycoproteins, proteoglycans, and salivary proteins. These components and structures collectively provide physical and biochemical support for tissue cells. At the macroscopic level, bone tissue is composed of the Haversian system, which contains vertical Haversian canals containing blood vessels and is surrounded by concentric plates of mineralized collagen, providing lumens for angiogenesis and creating conditions for the transport of various nutrients required for new bone formation. Due to the complexity of the bone tissue microenvironment's composition and structure, current bone tissue engineering scaffolds struggle to accurately represent the bone from its microscopic composition to its macroscopic structure. Therefore, developing a bone regeneration scaffold that can restore and summarize the natural characteristics of bone tissue at multiple levels may be of great significance for promoting new bone regeneration and structural restoration at bone defect sites.
[0003] Among related technologies, decellularized matrix (dECM) materials have attracted widespread attention from researchers due to their unique composition and structural advantages. Bone tissue-derived dECM retains bioactive components such as collagen, non-collagenous proteins, and glycosaminoglycans from bone tissue, encompassing to some extent the chemical composition of the organic part of bone. It plays a crucial role in bio-induction and tissue remodeling processes and is virtually immunogenic, making it considered an ideal material for bone tissue engineering. However, during extraction, to effectively remove immunogenic cellular components, bone tissue dECM requires pulverization and demineralization. This process removes almost all mineral components, severely disrupting the organic-inorganic composite structure of bone. As the most prominent feature of the complex hierarchical structure of bone, the organic-inorganic composite structure of bone tissue not only provides the structural basis for bone tissue function but also initiates many cellular signaling pathways in bone regeneration. Therefore, restoring the organic-inorganic composite structure of bone in dECM materials is of great significance for reshaping the natural microenvironment of bone tissue.
[0004] Based on this, the present invention develops a metal-doped biomimetic mineralized dECM crystal gel with an oriented structure for use in the regeneration and repair of vascularized bone tissue. Summary of the Invention
[0005] The first objective of this invention is to provide a method for preparing metal-doped biomimetic mineralized dECM crystal gel.
[0006] The second objective of this invention is to provide a metal-doped biomimetic mineralized dECM crystal gel.
[0007] The third objective of this invention is to provide the application of metal-doped biomimetic mineralized dECM crystal gel and its preparation method in the preparation of tissue repair materials.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] In a first aspect, the present invention provides a method for preparing metal-doped biomimetic mineralized dECM crystal gel, comprising the following steps:
[0010] S1. Hyaluronic acid and methacrylic anhydride are mixed in a solvent, the pH value is adjusted, and the reaction is carried out to obtain methacrylated hyaluronic acid.
[0011] S2. Under photoinitiator conditions, the methacrylated hyaluronic acid is mixed with decellularized extracellular matrix, and after freezing and cross-linking treatment, a crystal gel is obtained.
[0012] S3. Immerse the crystal gel in a solution containing Ca. 2+ and / or Mg 2+ The mineralized solution is then incubated with a buffer solution containing phosphate ions, followed by washing to obtain the final product.
[0013] According to some embodiments of the present invention, in step S1, the solvent includes water.
[0014] According to some embodiments of the present invention, the mass-to-volume ratio of the hyaluronic acid and the methacrylic anhydride is 1 g: 3-8 mL.
[0015] According to some embodiments of the present invention, the pH value is 8 to 9.
[0016] According to some embodiments of the present invention, the reaction time is 12 to 36 hours.
[0017] According to some embodiments of the present invention, the reaction further includes purification of the product after the reaction.
[0018] According to some embodiments of the present invention, in step S1, the degree of substitution of the methacrylamide group in the methacrylated hyaluronic acid is 45% to 55%.
[0019] According to some embodiments of the present invention, in step S2, the photoinitiator includes lithium phenyl-2,4,6-trimethylbenzoylphosphinate.
[0020] According to some embodiments of the present invention, the final concentration of the photoinitiator is 0.2-0.3%.
[0021] According to some embodiments of the present invention, in step S2, the decellularized extracellular matrix includes a bone-derived decellularized extracellular matrix.
[0022] According to some embodiments of the present invention, the method for preparing the bone-derived decellularized extracellular matrix includes the following steps:
[0023] 1) Obtain bone particles from the tibia, remove bone marrow, and then defatt the bone to obtain pre-decellularized bone matrix;
[0024] 2) The decellularized pre-bone matrix, trypsin, and EDTA were mixed and treated, washed, and then placed in a buffer solution containing penicillin / streptomycin for treatment. After lyophilization, white spongy particles were obtained.
[0025] 3) Mix the white spongy particles with an HCl solution containing pepsin, filter, collect the filtrate, and then collect the protein precipitate after salting out. The precipitate is then obtained after dialysis.
[0026] Preferably, the concentration of the trypsin is 0.01% to 0.1%.
[0027] Preferably, the concentration of EDTA is 0.01% to 0.1%.
[0028] Preferably, the buffer solution is PBS buffer, and the final concentration of penicillin / streptomycin is 0.8% to 1.2%.
[0029] Preferably, in the HCl solution containing pepsin, the concentration of pepsin is 0.8–1.2 mg / mL, and the concentration of HCl is 0.005–0.02 M.
[0030] Preferably, the solution used for the salting-out treatment is a 12% to 18% NaCl solution.
[0031] Preferably, the molecular weight cutoff for dialysis is 3200–3800 kDa.
[0032] According to some embodiments of the present invention, in step S2, the mass ratio of the methacrylated hyaluronic acid to the decellularized extracellular matrix is 1:0.5 to 1.5.
[0033] According to some embodiments of the present invention, in step S2, the crosslinking time is 2 to 20 minutes.
[0034] According to some embodiments of the present invention, the process prior to freezing also includes a mold shaping treatment.
[0035] According to some embodiments of the present invention, in step S3, the Ca in the mineralization solution 2+ The molar concentration is 6–12 mM.
[0036] According to some embodiments of the present invention, the Mg in the mineralization solution 2+ The molar concentration is 1–5 mM.
[0037] According to some embodiments of the present invention, the mineralization solution further comprises polyaspartic acid and Tris-HCl solution.
[0038] According to some embodiments of the present invention, the final concentration of polyaspartic acid in the mineralization solution is 0.01% to 0.2% (m / v).
[0039] According to some embodiments of the present invention, the pH value of the mineralization solution is 7.8-9.0.
[0040] According to some embodiments of the present invention, in step S3, the molar concentration of the phosphate ions in the buffer solution is 2 to 6 mM.
[0041] According to some embodiments of the present invention, in step S3, the incubation temperature is 37±2℃ and the incubation time is 5 to 10 days.
[0042] In a second aspect, the present invention provides a metal-doped biomimetic mineralized dECM crystal gel, which is prepared by the method described in the first aspect for preparing the metal-doped biomimetic mineralized dECM crystal gel.
[0043] A third aspect of the present invention provides a method for preparing metal-doped biomimetic mineralized dECM crystal gel as described in the first aspect, or the application of metal-doped biomimetic mineralized dECM crystal gel as described in the second aspect in the preparation of tissue repair materials.
[0044] The metal-doped biomimetic mineralized dECM crystal gel and its preparation method of the present invention have at least the following beneficial effects:
[0045] (1) The metal-doped biomimetic mineralized dECM crystal gel of the present invention has good ion release stability, which helps to upregulate a variety of osteogenic or angiogenic factors, and promotes osteogenic and vascularized bone regeneration by recruiting mesenchymal stem cells (MSCs), inducing osteoblast differentiation, and stimulating stem cell migration, differentiation and proliferation.
[0046] (2) The crystal gel of the present invention can significantly improve the migration ability of HUVECs, and the incorporation of Mg 2+Mineralized Mg-MCG crystals more effectively promote HUVECs migration. In addition, the Mg-MCG crystals prepared in this invention can upregulate the expression of H-type vessel markers in HUVECs in vitro, and the regeneration of H-type vessels can promote osteogenic-angiogenic coupling in the bone regeneration process, thereby achieving vascularized bone regeneration.
[0047] (3) The mineralized crystal gel prepared by the method of the present invention helps to promote the proliferation of rMSCs and improve their osteogenic differentiation potential. In addition, it also helps to increase cell adhesion and the expression of β1-, α5β1- and α3β1- integrins, thereby making the cytoskeleton morphology more spread out.
[0048] (4) The mineralized gel of the present invention uses directional cryocasting technology in preparation process. The gel obtained has an oriented interconnected macroporous structure, which simulates the Havers system, the basic structural unit of bone tissue, and provides favorable conditions for subsequent mineralization.
[0049] (5) This invention reports for the first time the construction of magnesium-doped biomimetic mineralized dECM crystal gel (Mg-MCG) with an oriented structure for vascularized bone tissue regeneration and repair. The Mg-MCG scaffold achieves a fine generalization of the composition and multilayer structure of natural bone from the microscopic to the macroscopic level, reproduces the vascular system in Haversian pores, and induces cells to grow in a directional manner along the oriented pore direction. It further promotes bone tissue regeneration and repair by promoting angiogenesis, and shows high biocompatibility, superior cell activity, and enhanced angiogenesis and osteogenic differentiation capacity, indicating its excellent application potential in bone tissue engineering.
[0050] Other features and advantages of the present invention will be set forth in the following description. Attached Figure Description
[0051] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0052] Figure 1 This is a schematic diagram illustrating the preparation of the Mg-MCG mineralized crystal gel of the present invention;
[0053] Figure 2 The histomorphological staining results of the natural bone tissue (Native) and dECM of the present invention are shown, where (a) is H&E staining and (b) is AB&NFR staining.
[0054] Figure 3 The results of quantitative analysis of natural bone tissue and dECM components in this invention are shown, where (a) is DNA, (b) is collagen, (c) is GAGs, and (d) is elastin.
[0055] Figure 4 This is the 1H NMR spectrum of the HAMA of this invention;
[0056] Figure 5 The results of scanning electron microscopy observation and elemental analysis of CG, MCG and Mg-MCG of the present invention are shown, where (a) is SEM and (b) is EDS mapping;
[0057] Figure 6 The results of thermogravimetric analysis of CG, MCG and Mg-MCG in this invention;
[0058] Figure 7 The infrared spectra of CG, MCG, and Mg-MCG of this invention are shown below.
[0059] Figure 8 The X-ray powder diffraction results of CG, MCG and Mg-MCG of the present invention are shown in (a) XRD pattern, (b) magnified pattern of (002) apatite related characteristic crystal plane, (c) magnified pattern of (211) crystal plane and (d) magnified pattern of (310) crystal plane.
[0060] Figure 9 TEM images of CG, MCG, and Mg-MCG of this invention and the orientation of HAp nanocrystals in mineralized fibers;
[0061] Figure 10 The equilibrium water content of CG, MCG and Mg-MCG in this invention;
[0062] Figure 11 These are the ion accumulation and release curves of CG, MCG, and Mg-MCG of the present invention, where (a) is the ion accumulation and release curve of Ca. 2+ (b) is Mg 2+ ;
[0063] Figure 12 The effects of CG, MCG and Mg-MCG on HUVECs migration are shown in the present invention, where (a) is a scratch healing diagram and (b) is a scratch healing statistics.
[0064] Figure 13 The results show the effects of CG, MCG and Mg-MCG on the formation of HUVECs tubes in this invention, where (a) is a tube formation diagram, (b) is a statistics of the number of connection points formed, and (c) is a statistics of the number of meshes formed.
[0065] Figure 14 The results show the effects of CG, MCG and Mg-MCG on the expression of EMCN and CD31 proteins in HUVECs. (a) is an immunofluorescence staining image, (b) is the statistical analysis of the average fluorescence intensity of EMCN, and (c) is the statistical analysis of the average fluorescence intensity of CD31.
[0066] Figure 15Live / Dead fluorescence staining and cell proliferation of rMSCs in CG, MCG and Mg-MCG, where (a) is fluorescence staining and (b) is cell proliferation;
[0067] Figure 16 This is an actin staining diagram of rMSCs in CG, MCG and Mg-MCG of the present invention;
[0068] Figure 17 The results of ALP staining and ALP activity quantification of rMSCs in CG, MCG and Mg-MCG are shown, where (a) is ALP staining and (b) is ALP activity quantification.
[0069] Figure 18 The results show the expression of osteogenic-related genes in rMSCs in CG, MCG and Mg-MCG, where (a) is ALP, (b) is RUNX2, (c) is OCN and (d) is COLⅠ. Detailed Implementation
[0070] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0071] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0072] In the embodiments of the present invention, the reagents and materials used are shown in Table 1.
[0073] Table 1: Reagents and Materials
[0074]
[0075]
[0076] In an embodiment of the present invention, the preparation method of the Tris-HCl solution with a pH of 7.4 is as follows:
[0077] Dissolve 1×Tris-HCl dry powder in 1.8L of deionized water, slowly add 1.0M HCl dropwise until the solution pH is 7.4, and then bring the volume to 2.0L.
[0078] The 4.2mM HPO4 used 2- The solution is prepared as follows: Accurately weigh 0.7308g of K2HPO4 solid into a beaker, add 950mL of Tris-HCl solution, and after complete dissolution, add 1M NaOH solution dropwise at room temperature to adjust the pH to 7.8-8, and finally bring the volume to 1.0L.
[0079] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0080] Example 1: Metal-doped biomimetic mineralized dECM crystal gel
[0081] This embodiment provides a method for preparing a metal-doped biomimetic mineralized dECM crystal gel with an oriented pore structure, as shown in the schematic diagram below. Figure 1 As shown, it specifically includes the following content.
[0082] 1. Preparation of methacrylated hyaluronic acid
[0083] Weigh 1.00 g of hyaluronic acid (HA) into a flask, add 100 mL of pure water, and stir at room temperature until completely dissolved. Then place the flask in an ice bath and quickly add 5.0 mL of methacrylic anhydride. Add 5.0 M NaOH dropwise to adjust the pH to 8-9 and maintain this pH for at least 4 hours. Continue the reaction on ice in the dark for 24 hours. Transfer the mixed solution to a dialysis bag (MWCO: 8.0 kDa) and dialyze against deionized water at 4 °C in the dark for 72 hours, changing the deionized water every 12 hours. Collect the solution in the dialysis bag and freeze-dry to obtain methacrylated hyaluronic acid (HAMA).
[0084] 2. Extraction of dECM
[0085] This embodiment uses a mild, surfactant-free method to extract bone dECM. The specific method is as follows:
[0086] Tibiae of newborn calves were purchased from slaughterhouses and stored at -80°C. The tibiae were sterilized by heating to 56-60°C in 0.9% NaCl saline for 3 hours. Soft tissue was removed, and the cancellous bone segment was sawn off using a bone saw. All cortical bone and cartilage were removed, and the bone was cut into small pieces. After flash freezing in liquid nitrogen, the pieces were crushed into bone particles no larger than 1.0 mm in diameter using a grinder. The particles were washed with PBS for 5 minutes to remove residual bone marrow, yielding pale yellow bone powder, which was then lyophilized overnight. The powder was stirred overnight at 300 rpm at a ratio of 1.0 g bone powder / 25 mL 0.5 M HCl at room temperature. After centrifugation (2000 rpm, 5 minutes) to remove the supernatant, milky white particles were obtained. These particles were washed with pure water for 10 minutes, blotted dry, and then soaked in a 1:1 chloroform:methanol mixture for 1 hour to defatt them. The particles were then washed repeatedly with methanol and pure water and lyophilized to obtain white decellularized pre-bone matrix (bDBM). bDBM was immersed in a solution containing 0.05% trypsin and 0.05% EDTA on a shaker (37°C, 100 rpm) for 24 h. After centrifugation (2000 rpm, 3 min) to remove the liquid, the solution was washed three times with PBS. The solution was then stirred overnight at 4°C in PBS containing 1% penicillin / streptomycin and freeze-dried to obtain white spongy particles.
[0087] To obtain dECM with good solubility and easy storage, the sponge-like particles were immersed in 0.01M HCl solution containing 1.0 mg / mL pepsin (1.0 mL of digestion solution was used for every 10 mg of sponge-like particles) and stirred (200 rpm) for 96 h until no visible solid fragments were visible. After filtering the solution through a 100-mesh filter, salting out was performed using 15% NaCl solution. The protein precipitate was collected by centrifugation (1000 rpm, 3 min), washed three times with cold PBS, and the precipitate was placed in a 3500 kDa dialysis bag and dialyzed in pure water for 3 days to obtain a completely clear and transparent protein solution. This solution was then lyophilized to obtain dECM.
[0088] 3. Preparation of crystal gels with oriented structures
[0089] Accurately weigh 0.05 g HAMA and 0.05 g dECM into a centrifuge tube, add 5.0 mL of PBS containing 0.25% LAP, and stir overnight at 4°C in the dark until all solids are completely dissolved. Transfer 100 μL of the mixture to a 5.0 mm diameter mold made of copper plate and polytetrafluoroethylene, and freeze the solution completely using dry ice as a cold source. Crosslink the solution by irradiating it with 405 nm UV light for 5 min. After crosslinking, allow it to thaw at room temperature, then remove the crystal gel from the mold and soak it in PBS overnight to remove unreacted monomers and residual initiators.
[0090] 4. Mineralization of crystal colloids
[0091] The crystal gel prepared above was sterilized by soaking in 75% ethanol for 12 hours, then washed three times with Tris-HCl solution, and soaked in Tris-HCl solution for 2 hours before use.
[0092] During mineralization, the crystal gel was immersed in 100 mL of solution containing 9.0 mM Ca. 2+ Add an equal volume of 4.2 mL HPO3 to the mineralized solution. 2- The solution was incubated at 37°C for 7 days. After pouring out the solution, the sample was washed three times with pure water for 5 minutes each time. The sample was then freeze-dried and stored at -20°C for a long time, and labeled as MCG crystal gel.
[0093] It contains 9.0 mM Ca 2+ The preparation method of the mineralization solution is as follows: accurately weigh 0.999g of CaCl2 solid and 0.200g of polyaspartic acid (PAsp) solid into a beaker, add 950mL of Tris-HCl solution, and after complete dissolution, add 1.0M NaOH solution dropwise at room temperature to adjust the pH to 7.8-8.0, and finally make up the volume to 1.0L.
[0094] Example 2: Metal-doped biomimetic mineralized dECM crystals
[0095] This embodiment provides a method for preparing a metal-doped biomimetic mineralized dECM crystal gel with an oriented pore structure. The method differs from Example 1 in the mineralization step, but the rest is the same. The mineralization step is as follows:
[0096] During mineralization, the crystal gel was immersed in 100 mL of solution containing 9.0 mM Ca. 2+ and 3.0mM Mg 2+ Add an equal volume of 4.2 mM HPO3 to the mineralized solution. 2- The solution was incubated at 37°C for 7 days. After pouring out the solution, the sample was washed three times with pure water for 5 minutes each time. The sample was then freeze-dried and stored at -20°C for a long time, and labeled as Mg-MCG crystal gel.
[0097] It contains 9.0 mM Ca 2+ and 3.0mM Mg 2+ The preparation method of the mineralization solution is as follows: accurately weigh 0.999g CaCl2 solid, 0.285g MgCl2 solid and 0.200g PAsp solid into a beaker, add 950mL Tris-HCl solution, and after complete dissolution, add 1.0M NaOH solution dropwise at room temperature to adjust the pH to 7.8-8.0, and finally make up the volume to 1.0L.
[0098] Comparative Example 1: Unmineralized Crystalline Gel
[0099] This embodiment provides a method for preparing unmineralized crystalline gel (CG). The method differs from that in Example 1 in that it does not undergo mineralization treatment, but is otherwise the same. The resulting product is labeled as CG crystalline gel.
[0100] Example 1: Histological staining analysis and quantitative component analysis of dECM
[0101] 1. Histological staining analysis of dECM
[0102] Histological staining analysis of the dECM prepared in Example 1 above and natural bone tissue was performed using a hematoxylin / eosin (H&E) staining kit, Alcian blue (AB) staining solution, and nuclear solid red (NFR) staining solution. The specific methods were performed according to the reagent instructions.
[0103] Histological staining results as follows Figure 2 As shown, the comparison confirms that dECM successfully decellularized while retaining some of the active components of natural bone tissue. Specifically, compared to natural bone tissue, H&E staining (such as...) showed... Figure 2 a) indicates that dECM effectively preserved the collagen components of bone tissue and successfully removed the nuclear components; AB&NFR staining results (e.g.) Figure 2 b) shows that dECM effectively preserves the glycosaminoglycans (GAGs) components of bone tissue, and the disappearance of nuclear solid red staining also proves that the nuclear components were effectively removed.
[0104] 2. Quantitative analysis of dECM components
[0105] To further evaluate the components in dECM, quantitative analysis was performed on the content of collagen, GAG, elastin, and DNA. Figure 3 The results showed that the DNA content in the dECM was 7.96±1.33 ng / mg, which is far below the requirement of <50 ng / mg for DNA content in the national standard GB / T16886; the collagen content was 648.33±39.15 μg / mg, the GAGs content was 5.73±1.53 μg / mg, and the elastin content was 5.66±0.57 μg / mg. This indicates that dECM with cellular components removed and tissue active components successfully preserved was obtained.
[0106] Example 2: Degree of Substitution of HAMA
[0107] The methacrylated hyaluronic acid prepared in Example 1 was subjected to 1H NMR spectroscopy analysis.
[0108] The results are as follows Figure 4As shown, characteristic peaks 1 and 2 (5.67 ppm and 6.11 ppm) of the double bond on the methacryloyl group appear in the 1H NMR spectrum, indicating that the methacryloyl group has been successfully modified onto hyaluronic acid. Characteristic peaks 3 (1.87 ppm) and 4 (1.94 ppm) belong to the methyl groups on the methacryloyl group and the methyl groups on the hyaluronic acid group, respectively. The degree of substitution of the methacryloyl group is calculated to be approximately 50.9% based on the peak areas of characteristic peaks 1, 2, 3, and 4.
[0109] Example 3: Microstructure and mineralization characterization of mineralized crystal gel
[0110] The microstructure of CG, MCG, and Mg-MCG prepared in the above embodiments and comparative examples was characterized, specifically including the following:
[0111] 1. Observation using a scanning electron microscope
[0112] CG, MCG, and Mg-MCG samples were cut along the coronal plane, freeze-dried, and then pasted onto conductive adhesive. After being sprayed with fine gold, the cross-section of the porous scaffold was observed by SEM, and the composition of the samples was analyzed by an elemental analyzer (EDS) with an accelerating voltage of 20.0 kV.
[0113] The results are as follows Figure 5 As shown, where Figure 5 Figure 'a' shows the cross-sectional structures of CG, MCG, and Mg-MCG, clearly revealing the orientation characteristics and pore size distribution of each sample's channels. The results indicate that the channels within the crystal gel are almost parallel, exhibiting good orientation. Statistical analysis showed that the average pore diameters of CG, MCG, and Mg-MCG were 92.51±35.18 μm, 87.51±15.10 μm, and 81.89±13.60 μm, respectively. The interconnected large pores allow cell growth into the crystal gel and facilitate the exchange of nutrients and metabolic waste during cell growth. Furthermore, it was observed that the MCG and Mg-MCG samples, after mineralization using the PILP method, were partially infiltrated by minerals, exhibiting a uniform and densely distributed needle-like distribution on the scaffold surface, without any nodular mineral deposits. However, due to the presence of Mg... 2+ The introduction of [a specific substance] partially inhibits mineralization, resulting in a decrease in mineral content on the Mg-MCG surface and a slight reduction in the size of surface mineralized crystals. EDS Mapping results (e.g.) Figure 5 b) shows that there are a large number of Ca and P elements on the surface of MCG and Mg-MCG, while the C, O and N elements are reduced accordingly. This indicates that the mineralization of the crystal gel was successfully achieved by the PILP method. The presence of Mg element in Mg-MCG also indicates that the Mg-containing mineralization of the crystal gel was achieved by the PILP method.
[0114] 2. Thermogravimetric analysis (TGA)
[0115] Thermogravimetric analysis (TGA) was used to determine the mineral content of CG, MCG, and Mg-MCG samples. The samples were ground in pure water using a grinding rod, then freeze-dried, and 10 mg of powder was taken for testing. Test conditions were: air atmosphere, 25-800℃, heating rate 10℃ / min, gas flow rate 40 mL / min. Mineral content was defined as the residual mass of the sample after the organic matter burned to a plateau.
[0116] Thermogravimetric analysis results are as follows Figure 6 As shown, the residual mass of CG decreases to 0 at around 600℃, and after heating to 800℃, the residual mass of MCG decreases to 60%, while that of Mg-MCG decreases to 48%. This indicates that the inorganic mass fraction (CaP minerals) in MCG is approximately 60.03%, and the mineral content in Mg-MCG, due to the slightly reduced inhibitory effect of Mg ions on mineralization, is approximately 48.29%, which is close to the mineral content in natural bone tissue. This result also suggests that mineralization may occur within the crystalline matrix, as mineral content tends to be lower when mineralization occurs only on the surface.
[0117] 3. Fourier Transform Infrared Spectroscopy (FTIR)
[0118] The sample to be tested was ground in pure water using a grinding rod, then freeze-dried. 10 mg of the powder was then analyzed using a Fourier transform infrared spectrometer at 4000-400 cm⁻¹. -1 Detect the functional group information contained in CG, MCG and Mg-MCG.
[0119] FTIR spectra of CG, MCG, and Mg-MCG are as follows: Figure 7 As shown, each group of samples retained the typical absorption peak of dECM, namely the stretching vibration of νC=O (1634 cm⁻¹). -1 amide I band), δN-H bending vibration (1408 cm) -1 amide II band) and stretching vibration of νC-H (1237cm) -1 The absorption peak related to hyaluronic acid (amide III band) is 3314 cm⁻¹. -1 A broad peak of νO-H, 1150 cm⁻¹ -1 1050cm -1 And 940cm -1 Characteristic absorption peaks of carbohydrates. With the introduction of mineral phases, the absorption peaks associated with hyaluronic acid in dECM are significantly reduced, and due to the higher mineral content, the intensity of the associated absorption peaks in MCG decreases even more significantly, while the associated peaks of apatite, such as at 1025 cm⁻¹, remain relatively stable. -1 561cm -1 PO4 3-The presence of absorption peaks further confirms the introduction of mineral phases. Compared to MCG, the main apatite band in Mg-MCG is located at 561 cm⁻¹. -1 The widening and decreased strength indicate a reduced crystallinity of the mineral phases formed within the scaffold.
[0120] 4. X-ray powder diffraction (XRD)
[0121] The sample to be tested was ground in pure water using a grinding rod, then freeze-dried. 10 mg of the powder was taken and scanned using an X-ray diffractometer under the conditions of 40 kV voltage and 40 mA current, using CuKα radiation, with a scan rate increasing by 0.026° every 0.36 s, in the range of 10-80°.
[0122] XRD results are as follows Figure 8 As shown, the XRD patterns of both MCG and Mg-MCG samples exhibit characteristic diffraction peaks of hydroxyapatite, including those corresponding to the (002), (211), and (310) crystal planes. With the mineralization process, Mg... 2+ The introduction of this factor shifts the peak center positions of the (002), (211), and (310) crystal planes to higher 2θ values. Figure 8 (bd in the middle). This is due to Mg 2+ The size is smaller than Ca 2 + The d-interval of these planes varies with the amount of Mg in the mineralization solution. 2+ The effect decreases with the introduction of Mg. It is also noteworthy that Mg-MCG exhibits a broader peak compared to MCG-free MCG, indicating that the effect decreases with the introduction of Mg. 2+ When incorporated into the mineral lattice, the crystallinity of the mineral decreases, which corroborates the results of FTIR.
[0123] 5. Transmission electron microscopy and selected area electron diffraction
[0124] To analyze the mineralization characteristics of MCG and Mg-MCG crystal gels, the samples were observed using transmission electron microscopy (TEM). Since intact samples could not be directly scanned with TEM, ultrathin sections were required. The scaffold was frozen in liquid nitrogen, rapidly ground, freeze-dried, and a small amount of powder was impregnated with epoxy resin and polymerized at 60°C for 72 hours. After smoothing the sample surface, the sample was sliced into 70 nm sections using an ultramicrotome and received with a copper mesh. The sections were observed under TEM at an accelerating voltage of 120 kV, and the crystal morphology of the forming minerals was analyzed using selected area electron diffraction (SAED).
[0125] The morphology of mineralized fibers in MCG and Mg-MCG is as follows: Figure 9 As shown, the TEM images reveal a clear dark contrast between the mineralized and unmineralized groups, confirming that the MCG and Mg-MCG have been thoroughly infiltrated by minerals, achieving intrafibrous mineralization, and that Mg... 2+ The doped mineralized HAp crystals were more uniformly distributed in the fibers, which is similar to previous findings. SAED mode was used to study the orientation characteristics of HAp nanocrystals in collagen fibers. The arc-shaped arrangement of MCG and Mg-MCG in the (002) plane indicates that the obtained mineralized HAp nanocrystals are aligned along the (001) direction, matching the orientation of minerals within bone fibers. 2+ Doping did not adversely affect the arrangement of mineralized HAp crystals within the fibers. This result indicates that minerals penetrate the interior of the scaffold material, encapsulating this key feature of the collagen-apatite bone nanostructure.
[0126] 6. Equilibrium moisture content
[0127] The equilibrium water content (EWC) of CG, MCG, and Mg-MCG samples was calculated by gravimetric method according to the following formula.
[0128] EWC%=((m w -m d )) / (m w ×100);
[0129] After soaking the crystal gel in pure water for 2 days to reach swelling equilibrium, the surface water was wiped off with filter paper, and the weight was recorded as the wet weight m. w The mass of the sample after freeze-drying is recorded as the dry weight m. d .
[0130] EWC results for CG, MCG, and Mg-MCG are as follows: Figure 10 As shown, the EWC of CG is 98.04±0.17%, while the EWC of MCG and Mg-MCG decreases slightly due to mineralization, but still maintains a high EWC, preserving the advantage of high water content of hydrogels in tissue engineering. The EWC of MCG is 96.39±0.53%, while that of Mg-MCG is 97.42±0.15%, which further confirms that the mineralization degree of Mg-MCG is slightly lower than that of MCG.
[0131] Example 4: Ion release from mineralized crystal gel
[0132] Based on Mg 2+Sustained release of these substances can upregulate various osteogenic or angiogenic factors, promoting osteogenic and vascularized bone regeneration by recruiting mesenchymal stem cells (MSCs), inducing osteoblast differentiation, and stimulating stem cell migration, differentiation, and proliferation. This test example describes the ion release detection of the crystalloids prepared in the above examples and comparative examples. Specifically, it includes the following:
[0133] 1. Sample preparation
[0134] 10 mg of CG, MCG, and MG-MCG samples were immersed in 5.0 mL of PBS containing 0.02% sodium azide and placed on a shaker at 37°C. 200 μL samples were collected at days 1, 3, 5, 7, 10, 14, and 21, with an equal volume of PBS added each time. The harvested release was centrifuged (5000 rpm, 2 min), and the supernatant was used to test for Ca. 2+ and Mg 2+ content.
[0135] 2. Calcium ion release
[0136] Ca 2+ The content was determined using a calcium assay kit (MTB microplate method). 2+ The concentration determination steps are as follows:
[0137] (1) Configure Ca 2+ Standard solution: 2.5 mmol / L Ca2+ was diluted with deionized water. 2+ The standard solution was diluted 2.5 times to achieve a final concentration of 1.0 mmol / L.
[0138] (2) Preparation of working solution: Mix MTB reagent and alkaline reagent 2 in a ratio of 1:2 until homogeneous, and use immediately after preparation.
[0139] (3) Set up blank wells, standard wells and test wells in a 96-well plate. Blank well: add 10 μL of deionized water and 250 μL of working solution; Standard well: add 10 μL of standard solution and 250 μL of working solution; Test well: add 10 μL of sample and 250 μL of working solution.
[0140] (4) After mixing thoroughly, let stand for 5 minutes, and then measure the absorbance at 610 nm using an ELISA reader (i.e., A). 测定 A 标准 and A 空 (White), and determine Ca according to the following formula. 2+ Content, and plot Ca 2+ The cumulative release curve characterizes the Ca of the stent. 2+ Release characteristics.
[0141] Calcium ion content (mmol / L) = ((A) 测定 -A 空白 )) / ((A标准 -A 空白 ))×C 标准 ;
[0142] C 标准 Ca 2+ Standard concentration: 1.0 mmol / L.
[0143] 3. Release of magnesium ions:
[0144] Mg 2+ The content was determined using a magnesium ion detection kit (methyl thymol blue colorimetric method). 2+ The concentration determination steps are as follows: (1) Prepare Mg 2+ Colorimetric working solution: Mix an appropriate amount of Mg Assay Buffer with an equal volume of MTB colorimetric solution, and prepare immediately before use. (2) Select dry test tubes treated with dilute hydrochloric acid and rinsed with deionized water, and set up blank tubes, standard tubes and test tubes. Blank tube: Add 50 μL of deionized water and 2.0 mL of Mg Assay Buffer. 2+ Colorimetric working solution; Standard tube: Add 50 μL magnesium standard and 2.0 mL Mg 2 + Colorimetric working solution; Test tube: Add 50 μL of sample solution and 2.0 mL of Mg 2+ Colorimetric working solution. (3) Measurement: After blowing and mixing evenly, let stand at room temperature for 5 minutes. The solution color is light blue-purple. Zero the instrument with a blank tube. The optical path of the cuvette is 1 cm. Measure the absorbance at 600 nm in the standard tube and the measuring tube (i.e., A). 测定 A 标准 ), and determine Mg according to the following formula 2+ Content, and plot Mg 2+ The cumulative release curve characterizes the Mg in the stent. 2+ Ion release characteristics.
[0145] Magnesium ion content (mmol / L) = A 测定 / A 标准 ×C 标准 ;
[0146] C 标准 Mg 2+ The concentration of the standard was 0.823 mmol / L.
[0147] Ca in CG, MCG, and Mg-MCG 2+ Mg 2+ Release curve as shown Figure 11 As shown, CG does not contain minerals, and Ca was not detected. 2+ Mg 2+ The release of MCG and Mg-MCG in PBS, and the Ca 2+The release showed a similar, continuous trend, with Ca increasing over time. 2+ The release rate of [a substance] slows down relatively, but continues to be released even after 21 days. It is worth noting that Ca in MCG [is present in certain substances]. 2+ Release was slightly higher than that of Mg-MCG; at 21 days, the 21-day cumulative Ca of MCG was... 2+ The release concentration was approximately 1.18 mmol / L, and the cumulative Ca of Mg-MCG was... 2+ The release concentration was approximately 0.98 mmol / L. This difference is due to the higher degree of mineralization of MCG, i.e., a higher Ca content, thus MCG releases more Ca. 2+ The rate is higher. And as expected, Mg in Mg-MCG 2+ Showing similarity to Ca 2+ Similar release patterns, and consistent, stable release throughout the process, with a cumulative Mg content of 21 days. 2+ The release amount was approximately 0.62 mmol / L. These results indicate that Mg... 2+ It was well incorporated into the structure of PILP-mineralized apatite, and Ca in Mg-MCG 2+ Mg 2+ The total amount released is greater than that of Ca in MCG 2+ The total amount released is due to Mg 2+ The apatite with incorporated crystal structure has a lower crystallinity, resulting in a higher ion release rate.
[0148] Example 5: Experiment on the effect of mineralized crystals on HUVECs
[0149] Early angiogenesis is crucial in bone defect repair. This study investigated the effects of CG, MCG, and Mg-MCG scaffolds prepared in the above-described embodiments and comparative examples on human umbilical vein endothelial cells (HUVECs), specifically including the following:
[0150] 1. Cultivation of HUVECs
[0151] HUVECs were proliferated and cultured in a constant temperature cell culture incubator using HUVECs growth medium, with the medium being changed every two days. When the confluence reached more than 80%, they were digested and passaged using trypsin.
[0152] 2. Angiogenesis experiment of HUVECs
[0153] CG, MCG, and Mg-MCG scaffolds were soaked in DMEM complete medium at a ratio of 100 mg / mL and placed on a shaker at 37.0 °C for 72 h. The extract was then collected.
[0154] 3. HUVECs scratch healing experiment
[0155] Scratch tests were performed to evaluate the effect of the gel on the migration of HUVECs. The specific method is as follows:
[0156] 5.0×10 4 HUVECs were seeded in 24-well plates. When the cell confluence reached 100%, a straight line was drawn through the middle of each well. Then, the growth medium was replaced with extract, and images of the scratch were taken using an inverted microscope at the set time points. The average width of the scratch was measured using ImageJ software, and the healing rate of the scratch was calculated.
[0157] The results are as follows Figure 12 As shown, HUVECs in the CG, MCG, and Mg-MCG groups underwent significant healing through migration within 12 hours. Statistical analysis revealed that the healing rate within 12 hours was approximately 52.19 ± 4.02% in the control group, approximately 77.04 ± 1.31% in the CG group, approximately 92.83 ± 1.46% in the MCG group, and approximately 99.11 ± 0.77% in the Mg-MCG group. This indicates that PILP-mineralized MCG and Mg-MCG crystal gels can significantly improve the migration ability of HUVECs, and the incorporation of Mg... 2+ Mineralized Mg-MCG crystals more effectively promote the migration of HUVECs.
[0158] 4. HUVECs Tube Formation Experiment
[0159] The effect of crystalloids on angiogenic differentiation of HUVECs was evaluated using a tubule formation assay. The specific method is as follows:
[0160] The matrix gel was thawed overnight at 4°C and kept on ice until needed. The 96-well plate and pipette tips were pre-cooled on ice under aseptic conditions. 30 μL of matrix gel was added to each well of the 96-well plate to completely cover the bottom surface, and incubated at 37°C for 30 min to achieve complete cross-linking. After digestion of the HUVECs, they were resuspended in extracts of CG, MCG, and Mg-MCG, respectively. 5.0 × 10⁻⁶ μL of matrix gel was added to each well. 3 HUVECs were inoculated onto a substrate gel and cultured at 37°C and 5% CO2 for 12 hours. Images were taken at set time points using an inverted microscope and analyzed using ImageJ software.
[0161] The results are as follows Figure 13As shown, at 8 hours, the MCG and Mg-MCG groups formed obvious tubular structures, while the CG group only formed branched structures with discontinuous tubular walls, and the control group showed almost no obvious tubular structures. Statistical analysis revealed that within 8 hours, the number of connection points and meshes in the CG and MCG groups were significantly higher than those in the control group, while the number of connection points and meshes in the Mg-MCG group was significantly higher than those in other groups. This further confirms that the incorporation of Mg-MCG crystalloid has a positive effect on angiogenesis.
[0162] 5. Immunofluorescence staining
[0163] The effects of different crystalloids on the expression of vascular-related markers CD31 and EMCN in HUVECs were evaluated by immunofluorescence staining. The specific methods are as follows:
[0164] CG, MCG, and Mg-MCG scaffolds were immersed in ECM complete medium at a ratio of 100 mg / mL and placed on a shaker at 37.0 °C for 72 h. The extract was then collected. Then 2.0 × 10⁻⁶ mol / L of the extract was added. 4 HUVECs were seeded at the bottom of a confocal dish. After the cells adhered, the growth medium was replaced with ECM complete medium or extract medium. Cells were cultured for 2 days, followed by immunofluorescence staining. The specific steps are as follows:
[0165] Fix with 4% paraformaldehyde for 30 min at room temperature, then treat with 1.0 mL of 0.1% Triton X-100 for 10 min. Add 1.0 mL of 1% BSA blocking buffer and treat for 30 min, then add 200 μL of primary antibody mixture (CD31 antibody (mouse anti-human) dilution: 1:300; EMCN antibody (rabbit anti-human) dilution: 1:200), and incubate overnight at 4°C. Wash three times with PBS to remove unbound antibody proteins, then add 200 μL of secondary antibody mixture (goat anti-rabbbit-488 dilution: 1:250; goat anti-mouse-647 dilution: 1:250) and incubate for 1 h. Wash three times with PBS to remove unreacted antibody proteins, then add 300 μL of DAPI staining solution and incubate at room temperature in the dark for 10 min. Finally, observe and photograph using a laser confocal microscope, and analyze and statistically calculate the average fluorescence intensity using ImageJ software.
[0166] Immunofluorescence staining results as follows Figure 14As shown, the Mg-MCG group exhibits higher fluorescence intensity of CD31 and EMCN proteins. ImageJ software analysis revealed that the fluorescence intensity of CD31 and EMCN proteins in the Mg-MCG group was significantly higher than that in the CG and MCG groups. This study indicates that the co-high expression of CD31 and EMCN proteins is a typical characteristic of H-type vessels, suggesting that Mg-MCG crystalloids can upregulate the expression of H-vessel markers in HUVECs in vitro.
[0167] The results above show that Mg-MCG crystals better upregulate the expression of H-type vascular markers in HUVECs in vitro, which may enable the coupling of angiogenesis and bone regeneration.
[0168] Example 6: Morphology and proliferation of rMSCs in mineralized crystal gel
[0169] For bone repair materials, excellent biocompatibility means that the implant can promote the proliferation and adhesion of osteoblasts in the bone defect environment and the integration of bone tissue with the implant material. Therefore, analyzing cell proliferation and adhesion and spreading on the scaffold reflects the biocompatibility of the crystalloid. This example tested the cell proliferation and differentiation capacity of rMSCs in the CG, MCG, and Mg-MCG prepared in the above examples and comparative examples, specifically including the following:
[0170] 1. Seeding and osteogenic culture of rMSCs
[0171] Rat bone marrow mesenchymal stem cells (rMSCs) cultured to passage P3 were seeded into crystalloids for osteogenic differentiation studies. The crystalloids were sterilized by soaking in 75% ethanol, followed by washing three times with sterile PBS for 30 min each time, and then soaked overnight in complete culture medium. The sterilized crystalloids were carefully placed on sterile filter paper to absorb the culture medium, ready for use. The rMSCs were digested and resuspended in growth medium to the desired cell suspension density. The crystalloids were placed in the cell suspension and gently shaken; the crystalloids rapidly absorbed the cell suspension and swelled. Afterward, they were placed in wells and incubated in a cell culture incubator for 2 h to allow initial cell adhesion. Then, 2.0 mL of growth medium was added to each well, and the cells were incubated in an incubator, with the culture medium changed every two days.
[0172] 2. Live and dead staining and proliferation of rMSCs
[0173] The cell density was configured to be 5.0 × 10⁶. 5 Cell suspensions of 1 × 10⁶ mL were washed three times with PBS at 37°C for 5 min each time on days 1, 3, and 7 after cell seeding. The crystalloids were then cut into thin sections, stained using a live / dead cell staining kit, and photographed for analysis. 4Cells were seeded at the bottom of 24-well plates, and crystalloid samples were placed in Transwell chambers for co-culture with the cells. After 1, 3, and 7 days of culture, the activity of rMSCs was measured using a CCK-8 assay kit, and their proliferation rate was calculated.
[0174] Live / dead staining results as follows Figure 15 As shown in Figure a, the number of green fluorescent spots in each group of samples significantly increased with the incubation time increasing from 1 day to 7 days, indicating significant proliferation of rMSCs. This suggests that the crystal gels in each group have good biocompatibility and can support the survival and proliferation of rMSCs in the crystal gel. (The last sentence appears to be incomplete and requires further context.) Figure 15 b) quantified the proliferation of rMSCs. The results showed that the absorbance of each group gradually increased over time, and rMSCs in all groups underwent significant proliferation. Compared with the control group, the CG group had a higher proliferation rate, which is because dECM and HAMA can promote stem cell proliferation. Compared with CG, the MCG group showed a significantly increased rMSC proliferation rate, which may be due to the presence of Ca in the mineralized crystal gel. 2+ The release of Mg-MCG increased the proliferation rate of rMSCs; compared with MCG, Mg-MCG showed a higher proliferation rate of rMSCs in mineralized gels, which may be due to the increased Mg content. 2+ The release of [the substance] can promote the proliferation of rMSCs. Therefore, Mg-MCG mineralized colloid promotes the proliferation of rMSCs better than MCG mineralized colloid. This is consistent with the results of Live / Dead staining.
[0175] 3. Cytoskeleton staining
[0176] Cell morphology reflects the cytocompatibility of biological materials and determines subsequent cell proliferation, differentiation, and eventual bone formation. The specific method for staining the cytoskeleton is as follows:
[0177] With a density of 5×10 5 rMSCs at a concentration of [number] cells / mL were seeded into crystalloid gel. After 3 days of culture, the cells were fixed with 4% paraformaldehyde for 30 minutes and sectioned as before. The cytoskeleton was stained with phalloidin, and the cell nuclei were stained with DAPI to characterize cell morphology. Fluorescence images were acquired using laser confocal microscopy, and orientation analysis was performed using ImageJ software with the OrientationJ plugin.
[0178] Cytoskeleton staining results as follows Figure 16 As shown, rMSCs in all groups adhered well and were spread out in a certain direction. Notably, compared to the unmineralized group, the cytoskeleton of rMSCs in the mineralized gel exhibited a slender and stretched morphology, which is due to extracellular Ca2+. 2+ The increase in concentration caused Ca 2+Increased influx activates myosin light chain phosphorylation, leading to actomyosin contraction and resulting in an elongated skeletal structure. Furthermore, rMSCs in the Mg-MCG group exhibit plate-like pseudopodia and a higher surface area compared to the MCG group, indicating that Mg... 2+ This increases the likelihood of rBMSCs spreading on mineralized gels, and it is speculated that this phenomenon may be due to Mg 2+ It increases cell adhesion and the expression of β1-, α5β1- and α3β1- integrins, thereby making the cytoskeleton morphology more spread out.
[0179] Example 7: Experiment on the effect of mineralized crystalloids on osteogenic differentiation of rMSCs
[0180] As a typical biomarker in the early stages of osteogenic differentiation, ALP plays a crucial role in bone matrix mineralization. This study investigated the effects of CG, MCG, and Mg-MCG prepared in the above-described examples and comparative examples on osteogenic differentiation. The details are as follows:
[0181] 1. Osteogenic culture of rMSCs in gel
[0182] In osteogenic induction-related experiments, a cell density of 5.0 × 10⁶ cells was configured. 6 The cell suspension was incubated with rMSCs in a crystalloid at a concentration of / mL for 24 hours. The growth medium was then replaced with osteogenic induction medium, and the medium was changed every 2 days.
[0183] 2. ALP staining
[0184] After osteogenic induction culture of CG, MCG, and Mg-MCG for 3, 7, and 14 days, the samples were rinsed with cold PBS, fixed with paraformaldehyde, and then the rMSCs in the scaffold were stained. Coronal sections of the stained samples were observed and photographed under a microscope.
[0185] ALP staining results are as follows Figure 17 As shown in Figure a, the blue staining in the crystalloid gradually increased with the extension of osteogenic induction time, with the Mg-MCG group showing the most blue staining. This indicates that the expression level of ALP in each group gradually increased with the increase of induction time, while the ALP expression level in the Mg-MCG group was the highest. It is worth noting that all staining showed a directional distribution along the crystalloid pores, which further proves that the microchannels in the crystalloid can support rapid directional cell infiltration. This directional distribution pattern of cells in the crystalloid is similar to the Havers system in natural bone tissue.
[0186] 3. Quantitative analysis of ALP activity
[0187] After osteogenic induction culture for 3, 7, and 14 days following cell seeding, CG, MCG, and Mg-MCG crystalloid samples were washed 2-3 times with cold PBS, placed in 1.5 mL centrifuge tubes, and 300 μL of pre-chilled PBS containing 0.2% Triton-X 100 was added. The scaffolds were then ground on ice using a sterile, enzyme-free tissue homogenizer and allowed to stand for 30 min. The supernatant was collected by centrifugation (7000 rpm, 5 min) for ALP activity and total BCA protein content detection.
[0188] ALP activity quantification results are as follows Figure 17 As shown in b, there was no statistically significant difference in ALP activity among the groups at day 3, and all were at low levels. At days 7 and 14 of osteogenic culture, the ALP activities of MCG and Mg-MCG were significantly higher than those of the CG group, with Mg-MCG exhibiting the highest ALP activity. This indicates that PILP mineralization can significantly enhance the ALP activity of rMSCs in the crystalloid, as the mineralized crystalloid can continuously release Ca2+. 2+ And with Mg 2+ The incorporation of Mg-MCG significantly increased ALP activity, consistent with ALP staining data. These results indicate that Mg-MCG has a greater potential to promote osteogenic differentiation of rMSCs.
[0189] 4. Expression of osteogenic-related genes
[0190] To further investigate the effects of rMSCs on osteogenic differentiation in different gels, the expression of four osteogenic-related genes, ALP, OCN, RUNX2 and COLⅠ, was analyzed after 7 and 14 days of in vitro osteogenic induction.
[0191] Osteogenesis-related gene expression results as follows Figure 18As shown, ALP, an early osteogenic gene, was highly expressed in rMSCs in the crystalloids of all groups at day 7, but decreased significantly at day 14. This differs from the result that ALP activity continued to increase at day 14. This may be because ALP protein accumulated in the crystalloid, and changes in ALP gene expression preceded ALP protein expression in the later stages of osteogenic differentiation. This resulted in increased ALP activity at day 14 compared to day 7, while ALP gene expression decreased at day 14 compared to day 7. Nevertheless, ALP expression in the Mg-MCG group was still significantly higher than in other groups at all time points. RUNX2, an important gene in osteogenic differentiation, can promote osteogenic differentiation of mesenchymal stem cells by promoting the expression of COLⅠ, OCN, and ALP. RUNX2 expression was highest in the Mg-MCG group at all time points, with the highest RUNX2 expression at day 7. However, RUNX2 expression decreased at day 14, further indicating that rMSCs in the crystalloid were in the later stages of osteogenic differentiation after day 14. COLⅠ and OCN, as marker genes in the later stages of osteogenic development, showed significantly higher expression levels in Mg-MCG compared to other groups at 7 days of osteogenic induction, and their expression levels further increased after 14 days. These results further indicate that mineralizing rMSCs with Mg-MCG can better induce osteogenic differentiation.
[0192] In summary, this invention provides a metal-doped biomimetic mineralized dECM gel, its preparation method, and its application. Specifically, firstly, this invention extracts and retains the active components of bone tissue from dECM, using it as a matrix for subsequent mineralization processes; then, HAMA is synthesized to reduce the electronegativity of the dECM collagen surface, promoting subsequent internal mineralization; next, HAMA and dECM are mixed and oriented macroporous gel is prepared using directional freezing technology, and then Mg... 2+ The PILP-induced mineralization process achieves biomimetic mineralization of the scaffold (approximately 50% mineralization) while preserving the oriented macroporous structure of the crystalloid. This highly aligned mineralization structure enables a microscopic-to-macroscopic biomimetic simulation of natural bone tissue structure and promotes vascularized bone regeneration by facilitating early angiogenesis and ingrowth during bone repair. In summary, the bone tissue-adaptive mineralized crystalloid developed in this invention offers a promising clinical approach for the regenerative repair of bone defects.
[0193] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A method for preparing a metal-doped biomimetic mineralized dECM crystal gel, characterized in that, Includes the following steps: S1. Hyaluronic acid and methacrylic anhydride are mixed in a solvent, the pH value is adjusted, and the reaction is carried out to obtain methacrylated hyaluronic acid. S2. Under photoinitiator conditions, the methacrylated hyaluronic acid is mixed with decellularized extracellular matrix, and after freezing and cross-linking treatment, a crystal gel is obtained. S3. Immerse the crystal gel in a solution containing Ca. 2+ and / or Mg 2+ The mineralized solution is then incubated with a buffer solution containing phosphate ions, followed by washing to obtain the final product.
2. The preparation method according to claim 1, characterized in that, In step S1, the solvent includes water; Preferably, the mass-to-volume ratio of the hyaluronic acid and the methacrylic anhydride is 1 g: 3-8 mL; Preferably, the pH value is 8-9; Preferably, the reaction time is 12–36 hours; Preferably, the reaction further includes purification of the product.
3. The preparation method according to claim 1, characterized in that, In step S2, the photoinitiator includes lithium phenyl-2,4,6-trimethylbenzoylphosphine; Preferably, the final concentration of the photoinitiator is 0.2-0.3%.
4. The preparation method according to claim 1, characterized in that, In step S2, the decellularized extracellular matrix includes bone-derived decellularized extracellular matrix.
5. The preparation method according to claim 4, characterized in that, In step S2, the mass ratio of the methacrylated hyaluronic acid to the decellularized extracellular matrix is 1:0.5 to 1.
5.
6. The preparation method according to claim 1, characterized in that, In step S2, the crosslinking time is 2 to 20 minutes; Preferably, the process further includes mold shaping before freezing.
7. The preparation method according to any one of claims 1 to 6, characterized in that, In step S3, the Ca in the mineralization solution 2+ The molar concentration is 6–12 mM; Preferably, the Mg in the mineralization solution 2+ The molar concentration is 1–5 mM; Preferably, the mineralization solution further comprises polyaspartic acid and Tris-HCl solution; Preferably, the pH value of the mineralization solution is 7.0-9.
0.
8. The preparation method according to claim 7, characterized in that, In step S3, the molar concentration of phosphate ions in the buffer solution is 2–6 mM.
9. A metal-doped biomimetic mineralized dECM crystal gel, characterized in that, It was prepared by the method described in any one of claims 1 to 8 for metal-doped biomimetic mineralized dECM crystal gel.
10. The method for preparing the metal-doped biomimetic mineralized dECM crystal gel according to any one of claims 1 to 8, or the application of the metal-doped biomimetic mineralized dECM crystal gel according to claim 9 in the preparation of tissue repair materials.
Citation Information
Cited By
Preparation method of blood-derived GeLMA-lignin bionic hydrogel scaffold
CN121338115A
A preparation method of a blood-derived gelma-lignin biomimetic hydrogel scaffold
CN121338115B